Preventing Neurodegeneration by Controlling Oxidative Stress: The Role of OXR1 - Volkert, Michael R.; Crowley, David J. (Frontiers in Neuroscience, 2020)
Parkinson’s disease, amyotrophic lateral sclerosis (ALS), diabetic retinopathy, and neuronal damage resulting from ischemia are among the notable neurodegenerative diseases in which oxidative stress occurs shortly before the onset of neurodegeneration and neuronal cell death. A shared feature of these diseases is the depletion of OXR1 (oxidation resistance 1) gene products shortly before the onset of neurodegeneration. In animal models of these diseases, restoration of OXR1 has been shown to reduce or eliminate the deleterious effects of oxidative stress induced cell death, delay the onset of symptoms, and reduce overall severity. Moreover, increasing OXR1 expression in cells with normal levels of OXR1 protein further increases oxidative stress resistance and reduces the onset of disease while showing no detectable side effects. Thus, restoring or increasing OXR1 function shows promise as a therapeutic for the treatment of multiple neurodegenerative diseases. This review examines the role of OXR1 in neurodegenerative diseases and its potential as a therapeutic in light of our current understanding of OXR1 function at the cellular and molecular level and proposes a possible cascade of molecular events linked to OXR1’s regulatory functions.